Cybersecurity : ambient technologies, IoT, and industry 4.0 implications - Kumar, Gautam; Singh, Prakash Om; Saini, Hemraj (Artificial intelligence (AI): elementary to advanced practices, 2021)
This edited book discusses the evolution of IoT and Industry 4.0 and brings security and privacy related technological tools and techniques onto a single platform so that researchers, industry professionals, graduate, postgraduate students, and academicians can easily understand the security, privacy, challenges and opportunity concepts and make then ready to use for applications in IoT and Industry 4.0